Equal Time for Equal Crime? Racial Bias in School Discipline - Ying Shi; Maria Zhu (Institute of Labor Economics (IZA), 2021)
Well-documented racial disparities in rates of exclusionary discipline may arise from differences in hard-to-observe student behavior or bias, in which treatment for the same behavior varies by student race or ethnicity. We provide evidence for the presence of bias using statewide administrative data that contain rich details on individual disciplinary infractions. Two complementary empirical strategies identify bias in suspension outcomes. The first uses within-incident variation in disciplinary outcomes across White and under-represented minority students. The second employs individual fixed effects to examine how consequences vary for students across incidents based on the race of the other student involved in the incident. Both approaches find that Black students are suspended for longer than Hispanic or White students, while there is no evidence of Hispanic-White disparities. The similarity of findings across approaches and the ability of individual fixed effect models to account for unobserved characteristics common across disciplinary incidents provide support that remaining racial disparities are likely not driven by behavior.
Keywords: I24; J15; 330; racial bias; exclusionary discipline